Sustainable electricity generation and farm-grid utilization from photovoltaic aquaculture: a bibliometric analysis - Amusa A.A.; Johari A.; Jalil A.A.; Abdullah T.A.T.; Adeleke A.O.; Katibi K.K.; Shitu I.G.; Alhassan M. (Springer Nature, 2025)
Photovoltaic (PV) aquaculture offers a promising solution for sustainable electricity generation for farm and grid utilization (SEG/FGU). This fusion of solar technology and aquaculture methods is crucial for sustainable food production and eco-friendly power and grid integration. However, there is a significant gap in research, with a lack of comprehensive studies that highlight current advancements, publication patterns, research focal points, key contributors, and future avenues for advancing FGU research. A bibliometric analysis of the SEG/FGU research based on Scopus data revealed a steady rise in publications due to environmental issues, research collaborations, and funding availability. China emerged as the top nation with the most articles published (18 articles and 240 citations) on SEG/FGU growth and development, with Alexander Golberg, Tel Aviv University (Israel), and the National Natural Science Foundation of China (NSFC) as prolific authors, institutions, and funders, respectively. China?s supremacy has been attributed to the availability of funding from significant programs like NSFC. Three prominent research focal points emerged: the integration of solar energy, agriculture, and desalination; the progression of PV technology within the renewable energy sector; and the intersection of aquaculture and ecological stewardship. The current research focus is on enhancing efficiency, developing effective energy storage solutions, and expanding the scope of applications for agricultural practices. However, significant research voids persist in sustainable aquaculture applications, designing and integrating hybrid PV systems, and achieving scalability in PV technology. ? The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University 2024.